PENGARUH PENERAPAN METODE PEMBELAJARAN INKUIRI TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the inquiry-based learning method on thecritical thinking skills of Grade X students at UPT SMA Negeri 5 Bone. The researchuses a quantitative approach with an ex post facto design. The subjects consist of33 students from class X.8, selected using a full sampling technique.Data were collected through a questionnaire using a Likert scale and then analyzedusing a simple linear regression test with the help of SPSS version 25.The results show that the implementation of the inquiry-based learning method hasa significant effect on students’ critical thinking skills, as indicated by a significancevalue of 0.000 (< 0.05) and a coefficient of determination (R²) of 0.392. This meansthat 39.2% of students’ critical thinking skills are influenced by the application of theinquiry method.Thus, it can be concluded that the inquiry-based learning method can be used asan alternative approach in teaching to encourage students to think critically andactively